Law in Changing Societies: Spectra of the COVID-19 and Industrial Economy Issues - Muhammad Bahrul Ulum (Indonesian Journal of Law and Society, 2021)
The Editorial Board proudly presents the recent publication of the Indonesian Journal of Law and Society Volume 2 Issue 1 (March 2021). It is the third issue that the journal has consistently and rigorously selected manuscripts for publication from March 2020. In this issue, the critical topics examined by the authors mainly deal with the recent discourses on the law in changing societies, which includes its impacts from COVID-19 to the way of the Indonesian government that strived for leveraging more investments to end up an industrial economy. In this second year, the Indonesian Journal of Law and Society covers five scholarly papers. This issue spans from Indonesia’s hegemony campaign in tobacco industries, Nigeria’s reproductive rights in the wake of the COVID-19 pandemic, Indonesia’s constitutional complaint against constitutional rights, Indonesia’s AI-based legislative drafting, to state institutions’ dispute settlement from the Newmont divestment case.